Пропавшая девушка - Герритсен Тесс (Звезды мирового детектива, 2018)
Экземпляры: п/ф (20200916) / Инвентарный номер: 55902 / Цена: 80.00 / Сис.шифр: И(Амер) / Авт.знак: Г 39 / ГРНТИ: 17.82 / ББК: 84(7Сое)